Psychological and pedagogical optimization tools for the volition behaviour of the over-fives - Zhurat, Yulya; Oliynyk, Mariya (My University, 2019)
Volitional behaviour is a complex psychological phenomenon, which requires a combination of internal (motivational) and external (educational) influence. As a psychological structure component, volitional behaviour has its components such as motivation, volitional actions that are formed in the process of the child’s cognitive activity. During the pre-school period of the child's development there is not only a new correlation of motives, but the motives themselves acquire another, a peculiar character i.e. they become mediated, capable of inducing the child's activities in accordance with the intention. Due to this, it becomes capable of conscious moral choice. The main forms of manifestation of child capacity are activity, behaviour, and communication with other people. There are determined three types of activity: physical, intellectual, communicative and three groups of indicators: speed, ergic and variability. The volitional sphere development of the preschool children personality takes place on the principle of the normative behaviour establishment. The dynamics of volitional behaviour at the stage of pre-school childhood is determined by the content of voluntary actions of children in various types of childhood activity and is developed in the individual characteristics of manifestation levels of the motivational and regulatory structural components of volitional behaviour in the over-fives.
Keywords: Volitional regulation; volitional behaviour; motivation; establishment